There's a bat on the balcony (big book) - Caraher, Kim; Sofilas, Mark (Nelson Australia South Melbourne, 1994)
When Jenny finds a bat on the balcony, a tree frog in the toilet, and other small animals all over the house, her brother Chris is too busy watching television to look and won't believe her